Australian pharmacy perspectives on increasing access to medicines through reclassification. Issue 2 (April 2019) - Mey, Amary; King, Michelle; Kelly, Fiona; Grant, Gary; Townshend, James; Baumann-Birkbeck, Lyndsee; Woods, Phillip; Hope, Denise
Objectives: Availability of medicines without prescription can increase consumers' timely access to treatment and promote self-management of minor ailments and adherence to long-term medications. Globally, access to relevant medicines has improved through increased reclassification of medicines from prescription to non-prescription availability. However, Australian reclassification lags behind countries with comparable health systems, and the factors influencing this are poorly understood. Methods: Semi-structured interviews were conducted during May 2015 to explore the perspectives of Australian pharmacists and support staff on future reclassification. Interview responses were transcribed verbatim, and the data were analysed thematically, primarily informed by the general inductive approach. Results: Participants identified a broad range of medicines as candidates for future reclassification by applying risk versus benefit judgements, assessing any medicines with potential for misuse and hazardous medicines as unsuitable. Key drivers for change in classification were underpinned by participants' desire to support consumers' management of minor ailments and adherence for those on long-term therapy. Barriers to reclassification were identified by pharmacy staff as internal, negatively impacting pharmacists' readiness for reclassification and external, negatively impacting the overall progress of change. Conclusions: While the research provided valuable insights to inform the ongoing discussion on future reclassification, a larger, more representative sample is needed to confirm these findings.